STUDYING THE EFFECTIVENESS OF FEED SUPPLEMENTS FOR DOGS AND CATS - Sapko, S. A. (Scientific Progress & Innovations, 2019)
Insufficient complete nutrition is a problem not only for humans, but also for animals, particularly domestic cats and dogs. Using well-balanced feed supplements may be one way of solving this problem. Balanced diet of animals should contain more than 600 nutrient components. Preventive, dietary and therapeutic properties of nutrition largely depend on their quantity and combination. The analysis of medical and veterinary special literature is conducted, in which the main active components of Profiline feed supplements are described. Profiline feed supplements for animals in different combinations, depending on the purpose have the following components (active components): brewer's yeast, extracts of: Abalon (Haliotis), green sponge molluscs (Perna Canaliculus), cranberries (Oxycóccus), topinambur (Helianthus tuberosus), lespedeza (Lespedeza capitata), Bidens (Bidens tripartita), white willow (Salix alba L.), vitamin-mineral complex (Vit A, Vit D3, Vit E, Vit B9, selenium, zinc, iron, magnesium, potassium, dicalcium phosphate), calcium citrate, L-tryptophan, biotin, collagen hydrolysate, taurine, complex of lyophilized probiotic bacterial culture. The study of hematological and biochemical parameters dynamics of animal blood at adding one or another component to the diet is a significant indicator of the functional state of the pets’ organism. A lot of research is conducted on this issue. Feed supplements and dietetic nutrition effectively solve the problems of cardiological, geriatric diseases, gastrointestinal and orthopedic problems. According to the analysis of the literature data it has been established that Profiline feed supplement ingredients in recommended doses are harmless and effective, and on the whole improve the absorption of feed nutrients, in particular − protein, minerals, fat-soluble vitamins, and lead to the restoration of metabolic reactions in animal’s organism as a result of feeding feed supplements.